Defining and Measuring Economic Development: A Literature Review and Outlook - Eli J. Levine; Michele Tantardini (Journal of Public and Nonprofit Affairs, 2023)
Economic development is an increasingly popular topic in different research areas. However, there is not a definite, categorical, and settled definition for economic development, nor a comprehensive measure that is agreed upon. This study aims to fill this gap through a literature review of the scholarly publications 1950–2020 in all the English-language peer-reviewed journals in the subject areas of public administration and development. On this basis, the article identifies 19 themes as well as 14 types of improvements around which it is possible to group this multi-faceted topic. Specifically, the article highlights for each of the identified themes and types of improvements how economic development is defined and measured. In addition to that, our review reveals issues and research questions that go unaddressed. We conclude the article by providing our recommendations in this regard.